2003
DOI: 10.1002/pd.556
|View full text |Cite
|
Sign up to set email alerts
|

Replicate real‐time PCR testing of DNA in maternal plasma increases the sensitivity of non‐invasive fetal sex determination

Abstract: Amplification of free fetal DNA in maternal plasma is a valid and rapid technique for predicting fetal sex in first- and second-trimester pregnancies and could allow the restriction of invasive sampling procedures to male fetuses at risk of X-linked disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 15 publications
1
43
0
Order By: Relevance
“…A previous study (43 ) demonstrated that increasing the number of sample replicates from three to six in a 50-cycle real-time PCR improved the rate of detection of male DNA in maternal plasma from 92.6% to 100%. In the present study, the PCR was run for 55 cycles to increase sensitivity sufficiently to detect fetal material in early first-trimester samples.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (43 ) demonstrated that increasing the number of sample replicates from three to six in a 50-cycle real-time PCR improved the rate of detection of male DNA in maternal plasma from 92.6% to 100%. In the present study, the PCR was run for 55 cycles to increase sensitivity sufficiently to detect fetal material in early first-trimester samples.…”
Section: Discussionmentioning
confidence: 99%
“…Technical advances, such as the development of quantitative real-time polymerase chain reaction, have allowed several groups to demonstrate a 100% sensitivity and specificity in the detection of male fetuses [23][24][25]. Free fetal DNA has been detected as early as the fifth week of pregnancy [24], but concentrations, and subsequently the sensitivity of the test, increase with advancing gestation.…”
Section: (Grade C Level Iv)mentioning
confidence: 99%
“…Khorram Khorshid et al, have done the same experiments on the normal pregnant women could able to predict fetal gender with 97.3% sensitivity using real time PCR on the same genes on the chromosome Y [33]. Hromadnikova I et al, demonstrated a sensitivity and specificity of 100% in 12 pregnancies at risk of Haemophilia, 11 haemophilia A and 1 haemophilia B, and 32 pregnancies at risk of chromosomal aneuploidies in the 10 th to 18 th weeks of gestation using TaqMan Real-Time PCR [34]. Bustamante-Aragones A et al, assessed fetal sex with an accuracy and specificity of 100% from a gestational age of 7 weeks by RealTime PCR analysis [35].…”
Section: Methodsmentioning
confidence: 99%